STIMULASI MEMBACA PERMULAAN ANAK MELALUI MEDIA MOVABLE ALPHABET - Yuni Dwi Suryani; Muharrahman (Program Studi Pendidikan Islam Anak Usia Dini, 2022)
This research used a literature study that examined the use of the Montessori movable alphabet media to stimulate children's early reading. The method used in this research is a qualitative method with descriptive type. Reading is a complex skill. For preschoolers who are in the 4-6 year age range letters and words are something abstract. Activities that use movable alphabet media help children to recognize knowledge and understanding of letters which are the main basis for the development of early reading. In addition, movable alphabet media also supports activities that are oriented towards children's learning principles that are hands on activity so that the learning that children get is meaningful. Based on the analysis of literature studies from various sources from reputable research articles and books, the use of movable alphabet media is very effective in supporting children's early reading stimulation.